ANALYSIS OF TEACHER STRATEGIES IN IMPLEMENTING STUDENT CHARACTER EDUCATION IN THE MERDEKA CURRICULUM - Nawang Sari, Septi; Tri Fadila, Ferina; Anggraini, Ria Nur; Andrian, Firma; Adi Wijaya, Satria Nugraha (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Character education in the independent curriculum is an alternative for producing studentgraduates who have the Pancasila profile. This character education has 6 values that aredeveloped, namely faith and devotion to God Almighty and noble character, global diversity,mutual cooperation, creativity, critical reasoning, and independence. This research aims todetermine teacher strategies in implementing student character education in the Merdekacurriculum. This research uses a qualitative approach with a literature study type ofresearch. The results of the research show that the strategies used by teachers inimplementing character education for students in class IV in the independent curriculum arestrategies for organizing preliminary activities, material delivery activities, classmanagement, use of learning media, and organizing closing activities. This strategy isintended as a step to implement character education in the Merdeka curriculum.